A Mathematical Model for Infection of the Human Body by the Effects of Coronavirus - Singh, Jitendra (International Journal of Scientific Research in Biological Sciences, 2021)
The effect of the coronavirus is increasing daily. The coronavirus has caught the whole world. The coronavirus has infected more than thousands of people and killed more than millions. If the coronavirus is not stopped, then the system of the population of the whole world will be shaken. We have accepted this coronavirus problem as a challenge. A guideline has been provided by Mathematical Modeling to rule out the effects of the coronavirus and to protect people from the coronavirus. We are confident that this guideline will act as a shield to protect the lives of all people from the coronavirus.